IMPLEMENTATION OF SIMULATION MODEL CHARACTER LEARNING VIDEO IMPLEMENTATION IN INTEGRATED ISLAMIC PRIMARY SCHOOL DURING THE COVID-19 PANDEMIC - Maulidyah Safruddin; Andi Prastowo (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2022)
The COVID-19 pandemic has made teachers consider choosing learning media so that students can be helped to understand the learning material provided even though learning is accepted online. The use of learning video media is an option for learning as a teacher option when learning online. This study aims to see the process of implementing learning video media carried out at SDIT Al Hikmah Pangkep during the covid-19 pandemic from the perspective of educators. The character learning in question is the 9 pillars of character given to students 15 minutes before learning begins. The method in this research is descriptive quantitative with an instrument in the form of a questionnaire distributed to educators via google form. The data analysis used in this study is descriptive statistics, namely analyzing data by describing or describing the data that has been collected as it is. The results of this study revealed that the majority of educators considered that the character learning video media was well implemented. Character learning videos can help educators to teach material related to good characters in life. The use of video media is also favored by students because it can help students study at home, motivate students to study. Through character learning videos, it can also stimulate students to find important information related to character building